Development of herbal-based orally disintegrating tablets from Moringa oleifera Lam. leaves - Ali, Muhammad Azhar (2016)
The Moringa oleifera Lam. is a plant from the Moringaceae family. There are about 13 species of the Moringaceae family, of which Moringa oleifera is the species most widely known. It is native to Hamalian regions of Pakistan, India. Moringa. Moringa oleifera leaves are rich in multivitamins, minerals, carbohydrates, anti-oxidants and amino acids, however, extreme bitter taste has caused its low acceptability. The aim of present study was to convert whole Moringa leaves as one of the advanced forms of pharmaceutical dosage such as the orally disintegrating tablet (ODT). In this purpose, Moringa leaves were dried under six different drying conditions as to study the effect of sunlight, drying duration and temperature on vitamins concentration and colour quality. Oven 50 °C drying treatment was found to be optimum in terms of best curve fitting of moisture ratio models, vitamins preservation and colour quality. The dried leaves were ground and the effect of moisture contents, particles shape and size on physical and flow properties of Moringa leaves powder were analysed using Box-Behnken technique. Moringa leaves powder prepared with a hammer mill having 5% moisture contents and 50 μm particles were selected as the optimum on the basis of flowability standards. A correlation (CoI = 0.26CI – 5.47) was established between conventional (Carr Index) and advanced (Cohesion Index) methods for measuring flowability of powders. Banana powder was used as natural superdisintegrant which is one of the main excipient in ODT. The banana powder was prepared using convection oven at 70 °C of 4 mm slice thickness. A comprehensive comparison of prepared banana powder with one of the most commonly used synthetic superdisintegrant, AcDiSol was also done to study its flowability, hardness and disintegration characteristics. Banana powder has superior disintegration properties than AcDiSol but lower in tensile strength. In present formulation, banana powder acts not only as superdisintegrant but also aflavouring and nutritious agent. The excipients, such as microcrystalline celelluose (MCC), mannitol, aspartame and vanilla were selected as binder, sweeteners and falvouring agents on the basis of their flowability, hardness and taste masking properties. Simplex Lattice Design of Design of Expert® 8.0 software was used to formulate mixtures of Moringa orally disintegrating tablets. Formulation contained Moringa leaves powder (40%), banana powder (10%), MCC (20%), mannitol (20%), aspartame (5%) and vanilla powder (5%) was selected as an optimum on the basis of Food and Drug Administration (FDA) and The International Pharmacopoeia standards for orally disintegrating tablets. The optimum formulation has hardness, disintegration time and friability of 30.15 N, 50 sec and 0.89%, respectively. The dissolution of formulated tablets was tested in distilled water and simulated saliva using dissolution models to study the dissolution behaviour of tablets when mix with water and swallow in the mouth. Korsmeyer-Peppas model described best the dissolution behaviour of Moringa Orally Disintegrating Tablet (MODT). The Korsmyer n value of optimum MOST was 1.128 in distill water which shows rapid disintegration of formulated tablets. The optimum MODT was found not very stable as it gained 5%-6% weight and hardnessmwas also reduced 85%-100% at 75% relative humidity levels. The acute and sub-acute toxicity of optimum formulation were tested on rabbits and found absolutely safe as no damage were observed in liver and kidney cells of rabbits treated with the highest dosage rate of 250 mg/kg body weight. The total theoretical cost including raw materials and processing of optimum MODT was USD 0.023 which is the lowest for any multivitamins available in the Malaysian market. Five tablets per day of MODT have a moderate amount of minerals, amino acids and can fulfil 100% Recommended Dietary Allowance (RDA) of vitamin A (0.6 mg/day) for adolescence. The present research work provides a fundamental understanding of tabletting characteristics of any herb and medicinal plant leaves powder in their pure form. It is the first report herbal based orally disintegrating tablet of any herbal and leaves powder of medicinal plant in combination with fruit powder.